Breastfeeding: a reproductive factor able to reduce the risk of luminal B breast cancer in premenopausal White women. Issue 3 (May 2017) - Giudici, Fabiola; Scaggiante, Bruna; Scomersi, Serena; Bortul, Marina; Tonutti, Maura; Zanconati, Fabrizio
Abstract : In the medical literature, the role of breastfeeding and reproductive factors in the risk of breast carcinoma is still an open debate in premenopausal women. We highlight the role of breastfeeding and reproductive factors in luminal A and luminal B, the most frequent breast cancers. This case–control study analyzes a White premenopausal population of 286 breast cancer patients, divided into molecular subtypes, and 578 controls matched by age. Multivariate logistic regression models were used to assess the relationships of breastfeeding and other reproductive factors (age at menarche, parity, age at first pregnancy, number of children) with the risk of breast cancers. Among the variables examined, reproductive factors did not alter the risk of cancer, whereas breastfeeding up to 12 months was a significant protective factor against luminal B breast cancer (multivariate odds ratio: 0.22, 95% confidence interval: 0.09–0.59, P =0.002). In contrast, luminal A cases did not significantly correlate with breastfeeding or other reproductive factors. Breastfeeding up to 12 months is strongly protective against the more aggressive luminal B, but not against the less aggressive luminal A breast cancer in premenopausal White women.